Antifreeze glycopeptide diastereomers - Nagel, Lilly; Budke, Carsten; Dreyer, Axel; Koop, Thomas; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2012)
Antifreeze glycopeptides (AFGPs) are a special class of biological antifreeze agents, which possess the property to inhibit ice growth in the body fluids of arctic and antarctic fish and, thus, enable life under these harsh conditions. AFGPs are composed of 4–55 tripeptide units -Ala-Ala-Thr- glycosylated at the threonine side chains. Despite the structural homology among all the fish species, divergence regarding the composition of the amino acids occurs in peptides from natural sources. Although AFGPs were discovered in the early 1960s, the adsorption mechanism of these macromolecules to the surface of the ice crystals has not yet been fully elucidated. Two AFGP diastereomers containing different amino acid configurations were synthesized to study the influence of amino acid stereochemistry on conformation and antifreeze activity. For this purpose, peptides containing monosaccharide-substituted allo-L- and D-threonine building blocks were assembled by solid-phase peptide synthesis (SPPS). The retro-inverso AFGP analogue contained all amino acids in D-configuration, while the allo-L-diastereomer was composed of L-amino acids, like native AFGPs, with replacement of L-threonine by its allo-L-diastereomer. Both glycopeptides were analyzed regarding their conformational properties, by circular dichroism (CD), and their ability to inhibit ice recrystallization in microphysical experiments.
Keywords: bioorganic chemistry; circular dichroism; glycopeptides; ice recrystallization; microwave chemistry